O professor e o mágico são o artista (The teacher and the magician are the artist) (Revista Apotheke, 2022)
This article endevors to delineate relationships between poetic figures belonging to the fields of visual arts, education and scientific research by establishing an open dialogue between these elements through the text "The artist, scientist and magician" by Luiz Camnitzer.
Keywords: artist; teacher; magician; trick